2019
DOI: 10.1111/luts.12253
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and persistence of mirabegron as a first‐line treatment in patients with overactive bladder in real‐life practice

Abstract: Objectives: To evaluate the effectiveness and persistence of mirabegron as a first-line treatment in patients with overactive bladder (OAB) in real-life practice. Methods:We retrospectively analyzed patients with OAB who received mirabegron (50 mg) as a first-line treatment. According to treatment course, patients were divided into three groups, (a) mirabegron only (monotherapy group), (b) mirabegron and anticholinergics (add-on group), and (c) mirabegron replaced with another treatment (switch group). The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…The previous studies were database analyses, while the present study was a clinical practice investigation. In support of this hypothesis, a retrospective, real‐life study found that treatment‐naïve patients persisted with mirabegron treatment longer than patients who had received previous anticholinergic therapy 38 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The previous studies were database analyses, while the present study was a clinical practice investigation. In support of this hypothesis, a retrospective, real‐life study found that treatment‐naïve patients persisted with mirabegron treatment longer than patients who had received previous anticholinergic therapy 38 …”
Section: Discussionmentioning
confidence: 90%
“…In support of this hypothesis, a retrospective, real‐life study found that treatment‐naïve patients persisted with mirabegron treatment longer than patients who had received previous anticholinergic therapy. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Again, this finding may be due to the fact that treatment‐experienced patients will be more familiar with the potential therapeutic benefits that can be achieved by taking OAB medication consistently. In contrast, a South Korean practice study found that treatment‐naïve patients persisted with mirabegron treatment longer than those who had received previous anticholinergic therapy 25 …”
Section: Discussionmentioning
confidence: 87%
“…In contrast, a South Korean practice study found that treatment-naïve patients persisted with mirabegron treatment longer than those who had received previous anticholinergic therapy. 25 Regardless of the subgroup, mirabegron was associated with longer persistence compared with all of the antimuscarinics investigated. In agreement with our findings, most of the studies that have investigated persistence according to specific subgroups found that mirabegron was associated with longer persistence than antimuscarinics regardless of the sex, age, or treatment status of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…3,6 According to the increasing interest in the association of aging with frailty, many researchers have suggested the clinical implication of frailty in several diseases. [7][8][9] Lower urinary tract symptoms including overactive bladder (OAB) are common urologic disorders in the elderly [10][11][12][13][14][15][16][17][18][19][20] and several studies have suggested an association of falls with OAB. 21 The OAB symptoms are the leading causes of sleep disturbance 13,22,23 and are associated with frailty.…”
Section: Introductionmentioning
confidence: 99%